The experience of high-frequency gambling behavior of older adult females in the United Kingdom: An interpretative phenomenological analysis. (4th May 2017) - Pattinson, Julie; Parke, Adrian
ABSTRACT: The prevalence of older adult female gambling participation and gambling disorder is increasing in the UK, and there is a paucity of published research available to understand possible risk factors for frequent gambling in this demographic. The aim of the current study was to identify and explore motivations and patterns of gambling behavior in high-frequency older adult female gamblers in the UK, from the perspective of the individual and in the context of their experience of aging. Ten UK older adult female high-frequency gamblers were recruited via stratified purposive sampling, with a mean age of 70.4 years. Data was collected via semistructured interviews and analyzed using interpretative phenomenological analysis. Three core themes representative of the experience of this phenomenon emerged from the transcripts, including: Filling voids, emotional escape, and overspending. The present study has provided a contextualized understanding of motivating factors and several age-related vulnerabilities that may account for high gambling frequency in this population.